Magnetism: Electricity’s Traveling Companion - Lindenfeld, Peter; Brahmia, Suzanne White; White Brahmia, Suzanne (Physics, 2011)
Electric charges are everywhere, but we rarely think about them or the electric forces between them. Magnetic forces are more familiar. We know them from toys and compasses, and we are aware that the earth is a giant magnet. But what gives rise to the magnetic forces? Is there something like the electric charges that are responsible for electric forces? Our first experience with this question may be with a compass needle and its north and south poles. If we have two of them, we see that a north pole attracts a south pole and repels another north pole, just